The gender pay gap in informal employment in Poland - Magdalena Rokicka; Anna Ruzik (Center for Social and Economic Research (CASE), 2010)
This paper addresses the issue of the gender pay gap in the formal and informal labour markets in Poland. The authors verify the hypothesis of the existence of a gender pay gap in informal work and compare this gap with the one observed in the formal (registered) labour market. Various analyses of available data show that size and characteristics of gender pay gap differ depending on the level of earnings. The inequality of earnings among unregistered women and men is more pronounced at the bottom tail of the earnings distribution. In the case of formal employees, inequality at the top of the distribution tends to be larger, confirming the existence of a "glass ceiling". The decomposition of the gender pay gap for selected quintiles indicates that it would be even higher if women had men's characteristics. A possible explanation of the results is the lack of minimum wage regulations in the informal market and the greater flexibility in agreement on wages in the higher quantiles.
Keywords: J31; O17; J71; 330; Gender pay gap; informal employment; quantile regression; Lohnstruktur; Geschlechterdiskriminierung; Arbeitsmarktdiskriminierung; Arbeitsmarkt; Informelle Wirtschaft; Polen